A Review of the Eriococcid Genera (Hemiptera: Sternorrhyncha: Coccoidea) of South America - Hodgson, Chris; Miller, Dug (Zootaxa, 2010)
This paper reviews the present status of all genera of Eriococcidae (Hemiptera: Sternorrhyncha: Coccoidea) known from South America and provides generic diagnoses based on the adult females of all available species for each genus. Redescriptions and illustrations are provided for the adult females of Aculeococcus morrisoni Lepage, Apiococcus gregarius Hempel, Capulinia sallei Signoret, Carpochloroides viridis Cockerell, Macracanthopyga verganiana Lizer y Trelles, Pseudocapulinia lanosa Hempel and Tectococcus ovatus Hempel, which are all type species of their respective genera. In addition, modified reproductions of original illustrations are provided for the adult females of the following species as representatives or type species of South American genera: Acanthococcus aceris Signoret, Chilechiton lynnae Hodgson & Miller, Chilecoccus browni Miller & González, Coxicoccus foldi Kozár & Konczné Benedicty, Eriobalachowskya valenzualae (Balachowsky), Exallococcus laureliae Miller & González, Hempelicoccus paranaensis (Foldi & Kozár), Icelococcus nothofagi Miller & González, Intecticoccus viridis Kondo, Melzeria horni Green, Orafortis luma Hardy, Oregmopyga neglecta (Cockerell), Poliloculus stipae González, Pseudotectococcus anonae Hempel and Stibococcus cerinus Miller & González. Descriptions and illustrations are also provided of the first-instar nymphs of: Acanthococcus aceris Signoret, Aculeococcus morrisoni, Apiococcus gregarius, A. singularis Hempel (which appears to be sexually dimorphic), Capulinia sallei, Carpochloroides viridis, Chilechiton lynnae, Exallococcus laureliae, Hempelicoccus tucumanensis (González & Granara de Willink), Icelococcus lithrae Miller & González, Melzeria horni, Oregmopyga peruviana Granara de Willink & Diaz, Pseudocapulinia lanosa, Pseudotectococcus anonae and Tectococcus ovatus. In addition, illustrated descriptions of the adult males of Capulinia sallei, Carpochloroides viridis, and Tectococcus ovatus are included. The first-instar nymphs and adult males of the other genera, where they are known, are also diagnosed and discussed. Based on the molecular studies of Cook & Gullan (2004), most species currently included in Eriococcus Targioni Tozzetti known from South America are considered to belong to the genus Acanthococcus Signoret, resulting in the following new combinations: A. clapsae (González) n. comb., A. cuneifoliae (González) n. comb., A. divaricatae (González) n. comb., A. pituilensis (González) n. comb. and A. lahillei (Leonardi) n. comb. In additon, Eriococcus pumuliae González, E. santiaguensis González & Granara de Willink and E. tucumanensis González & Granara de Willink are transferred to Hempelicoccus, as H. pumuliae (González) n. comb., H. santiaguensis (González & Granara de Willink) n. comb. and H. tucumanensis n. comb. (González & Granara de Willink). The status of Opisthoscelis prosopidis Kieffer & Jorgensen, the only species from the Neotropics currently included in Opisthoscelis Schrader, is discussed, and it is concluded that this species is unlikely to belong to this genus but is currently unrecognizable. Keys are provided for the identification of the 24 genera now known from South America based on the morphology of: (i) the adult females; (ii) the first-instar nymphs; and (iii) adult males, as far as these are known. In addition, Appendix 1 lists all Eriococcidae known from South America with their current generic placement, along with a brief summary of their host plants.